Utility of a screening tool for haemostatic defects in a multicentre cohort of adolescents with heavy menstrual bleeding. Issue 6 (12th September 2018) - Zia, Ayesha; Stanek, Joseph; Christian‐Rancy, Myra; Ahuja, Sanjay P.; Savelli, Stephanie; O'Brien, Sarah H.
Abstract : Introduction: Heavy menstrual bleeding (HMB) may be expected for many adolescents after menarche. Accurate assessment of HMB, a key component in the diagnosis of a haemostatic defect (HD), is a well‐recognized challenge. Aim: Our objective was to determine the diagnostic accuracy of an HMB‐specific screening tool for HDs in adolescents with HMB, presenting to a secondary care setting. Methods: Adolescents with HMB were evaluated for a HD at 4 US centres. A screening tool, the Philipp Tool, developed and validated in adult women with HMB, was administered. We modified the tool by assigning a score based on the number of affirmative responses. Sensitivity, specificity and likelihood ratios (LRs) of a positive tool, modified tool, with a pictorial blood assessment chart (PBAC) score >185, and with serum ferritin ≤20 ng/mL were calculated for HDs. Results: Among 248 adolescents with HMB, 29% were diagnosed with HDs. Sensitivity, specificity and LR of a positive screening tool for HDs were 95% (range 88‐99), 14% (9‐21) and 1.1 (1‐1.2), respectively. A score of ≥2, addition of a PBAC score >185 and ferritin ≤20 ng/mL changed the sensitivity, specificity and LR of the tool to 72% (61‐81), 94% (83‐99), 76% (65‐85); 60% (53‐68), 24% (16‐34) and 39% (31‐47) and 1.8 (1.4‐2.2), 1.2 (1.1‐1.4) and 1.2 (1‐1.4), respectively. Conclusion: Although sensitive, the discriminative ability of the tool to identify adolescents with HDs from those without, who presented with HMB, was low. Further research is needed to optimize or develop an adolescent‐specific HMB tool for secondary care settings.